Impact of a western diet on the ovarian and serum metabolome. (October 2016) - Dhungana, Suraj; Carlson, James E.; Pathmasiri, Wimal; McRitchie, Susan; Davis, Matt; Sumner, Susan; Appt, Susan E.
Highlights: A metabolomics study was done using archived ovarian tissue and serum from midlife cynomolgus monkeys that had been exposed to a prudent diet or a Western diet. Sixty-four metabolites were identified in serum and 47 metabolites were identified in ovarian tissue that differed by diet. Dietary exposure had a significant impact on the serum and ovarian metabolome, and demonstrated perturbation in metabolic pathways. Abstract: Objective: The objective of this investigation was to determine differences in the profiles of endogenous metabolites (metabolomics) among ovaries and serum derived from Old World nonhuman primates fed prudent or Western diets. Design: A retrospective, observational study was done using archived ovarian tissue and serum from midlife cynomolgus monkeys ( Macaca fasicularis ). Targeted and broad spectrum metabolomics analysis was used to compare ovarian tissue and serum from monkeys that had been exposed to a prudent diet or a Western diet. Monkeys in the prudent diet group (n = 13) were research naïve and had been exposed only to a commercial monkey chow diet (low in cholesterol and saturated fats, high in complex carbohydrates). Western diet monkeys (n = 8) had consumed a diet that was high in cholesterol, saturated animal fats and soluble carbohydrates for 2 years prior to ovarian tissue and serum collection. Outcome measures: Metabolomic analyses were done on extracts of homogenized ovary tissue samples, and extracts of serum. Targeted analysis was conducted using the Biocrates p180 kit and broad spectrum analysis was conducted using UPLC-TOF-MS, resulting in the detection of 3500 compound ions. Results: Using metabolomics methods, which capture thousands of signals for metabolites, 64 metabolites were identified in serum and 47 metabolites were identified in ovarian tissue that differed by diet. Quantitative targeted analysis revealed 13 amino acids, 6 acrylcarnitines, and 2 biogenic amines that were significantly (p < 0.05) different between the two diet groups for serum extracts, and similar results were observed for the ovary extracts. Conclusions: These data demonstrate that dietary exposure had a significant impact on the serum and ovarian metabolome, and demonstrated perturbation in carnitine, lipids/fatty acid, and amino acid metabolic pathways.